2020
DOI: 10.1055/a-1371-9359
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Awareness and Acceptance of Sonographically Diagnosed Epiploic Appendagitis (EA): A Retrospective Analysis of EA in a Single Tertiary Academic Referral Center

Abstract: Purpose To describe the clinical awareness and acceptance of ultrasound-diagnosed acute epiploic appendagitis (EA) and their importance to avoid unnecessary therapeutic and imaging measures. Patients and Methods The data were obtained of n=54 patients with acute, localized, peritonitic pain and EA diagnosed by B-mode ultrasound and contrast-enhanced ultrasound examination from November 2003 to September 2020. All examinations were performed by a German Society for Ultrasound in Medicine (DEGUM) Level III quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The high sensitivity and specificity of CEUS in the diagnosis of perfusion disturbance in incarcerated hernias demonstrate that CEUS should be considered a useful and cost-effective method without a radiation-exposing imaging modality. The findings of this study are in accordance with previous studies that showed that CEUS has a high diagnostic performance in the detection of perfusion disturbance [ 8 , 9 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Notably, the cause of NEAs in CEUS was an omental tissue fibrosis in four cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high sensitivity and specificity of CEUS in the diagnosis of perfusion disturbance in incarcerated hernias demonstrate that CEUS should be considered a useful and cost-effective method without a radiation-exposing imaging modality. The findings of this study are in accordance with previous studies that showed that CEUS has a high diagnostic performance in the detection of perfusion disturbance [ 8 , 9 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Notably, the cause of NEAs in CEUS was an omental tissue fibrosis in four cases.…”
Section: Discussionsupporting
confidence: 92%
“…A widely used and proven imaging modality in clinical practice for the detection of perfusion disturbances is contrast-enhanced ultrasound (CEUS) [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the management of patients with painful acute abdomen, computed tomography (CT) is accepted as extremely sensitive in the characterization of abdominal surgical pathologies but can cause adverse effects due to high ionizing radiation exposure and intravenous injection of contrast material. While CT reveals the diagnostic findings for EA, which is currently treated conservatively, it is also effective in discounting other intra-abdominal pathologies [5]. However, due to insufficient awareness and the probable reporting of EA cases at much lower rates than there are in reality, up to 64% are overlooked, including in CT reports [5].…”
Section: Introductionmentioning
confidence: 99%
“…While CT reveals the diagnostic findings for EA, which is currently treated conservatively, it is also effective in discounting other intra-abdominal pathologies [5]. However, due to insufficient awareness and the probable reporting of EA cases at much lower rates than there are in reality, up to 64% are overlooked, including in CT reports [5]. Nevertheless, it has been reported by centers experienced in gastrointestinal imaging that ultrasonography (US) could be a reserve diagnostic method before CT examination or in the presence of CT findings that are suspicious in respect of EA [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, magnetic resonance imaging (MRI), positron emission tomography–computed tomography (PET-CT), and B-mode ultrasound (US) are used for evaluating MMs [ 2 , 3 , 9 , 10 ]. As a new trend in US imaging, contrast-enhanced ultrasound (CEUS) is used to assess perfusion patterns of various pathologies, including MMs [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Another new trend in US imaging is US elastography, which is a non-invasive tool for assessing tissue stiffness, with guidelines available for hepatic and non-hepatic applications [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%